Effect of population size on viable seed output, seed rand and natural regeneration pattern of a tropical conifer Widdringtonia whytei-Rendle in Malawi - Chanyenga, Tembo Faera (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD(For))--Stellenbosch University, 2013.